Identification of Roof Shapes that Suitable for Buildings on Bangunharjo Street Corridor According to Public Perception - Anashia Merliana Satriani; Maria Immaculata Ririk Winandari (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
Physical elements are the most easily observed and give visual impression that can absorbed by human memory. Physical element is formed by row of façade elements. Roof is the one of façade elements that very dominant form character. Bangunharjo is a corridor that dominant by residental functions in Semarang, Indonesia. Commercial demands and land efficiency make change to façade. Some of these changes adjust according to the perceptions of designers and buiding owners. But, the suitability of building and shape of façade elements must be assessed according to public perceptions. This study aims to find the shape of façade elements, especially roofs which suitable for Bangunharjo street corridor according public perception.The method of discussion is a quantitative method with a visual perception approach. For the result of the analysis it was found that the roof shape that most suitable for buildings on Bangunharjo is pelana (saddle roof) and limasan (pyramid roof).